Enhancing Microwave Absorbing Properties of Nickel-Zinc-Ferrite with Multi-walled Carbon Nanotubes (MWCNT) Loading at Higher Gigahertz Frequency - Fadzidah, Mohd Idris; Khamirul Amin, Matori; Ismayadi, Ismail; Idza Riati, Ibrahim; Rodziah, Nazlan; Mohd Shamsul Ezzad, Shafie (USIM PRESS, 2021)
The rapid growth of electronic systems and devices operating within the gigahertz (GHz) frequency range has increased electromagnetic interference. In order to eliminate or reduce the spurious electromagnetic radiation levels more closely in different applications, there is strong research interest in electromagnetic absorber technology. Moreover, there is still a lack of ability to absorb electromagnetic radiation in a broad frequency range using thin thickness. Thus, this study examined the effect of incorporating magnetic and dielectric materials into the polymer matrix for the processing of radar absorbing materials. The experiment evaluated the sample preparation with different weight percentages of multi-walled carbon nanotubes (MWCNT) mixed with Ni0.5Zn0.5Fe2O4 (Nickel-Zinc-Ferrite) loaded into epoxy (P) as a matrix. The prepared samples were analysed by examining the reflectivity measurements in the 8 – 18 GHz frequency range and conducting a morphological study using scanning electron microscopy analyses. The correlation of the results showed that different amounts of MWCNT influenced the performance of the microwave absorber. As the amount of MWCNTs increased, the reflection loss (RL) peak shifted towards a lower frequency range and the trend was similar for all thicknesses. The highest RL was achieved when the content of MWCNTs was 2 wt% with a thickness of 2 mm with an RL of – 14 dB at 16 GHz. The 2.5 GHz bandwidth corresponded to the RL below -10 dB (90% absorption) in the range of 14.5 – 17 GHz. This study showed that the proposed experimental route provided flexible absorbers with suitable absorption values by mixing only 2 wt% of MWCNTs.